Advances and issues in fraud research: a commentary. Issue 1 (2nd January 2020) - Ozili, Peterson K.
Abstract : Purpose: This purpose of this paper is to discuss some observations in the forensic accounting-based fraud literature. The authors identify recent advances in the literature and highlight several important issues that are worth noting. Design/methodology/approach: The authors use a commentary analysis. Findings: The main message of this commentary paper is that fraud is complicated, and fraud complexity can significantly impact the way researchers undertake forensic accounting-based fraud research. Practical implications: The practical implication is that forensic accountants and forensic accounting researchers should incorporate into their practice the complexity of fraud regardless of whether they follow an empirical, experimental, exploratory, analytical or critical approach to fraud investigation. Originality/value: In contrast to previous studies, this study identifies the most recent issues emerging in fraud literature.